Profitability Moderates the Effect of Company Growth, Business Risk, Company Size, and Managerial Ownership on Capital Structure - Ferliana, Nia; Agustina, Linda (Accounting Analysis Journal, 2018)
The aims of this research to analyze the effect of company growth, business risk, firm size, and managerial ownership to capital structure with profitability as moderating variable. The population of research are 66 all industrial and chemical companies listed in Indonesia Stock Exchange (BEI) year 2013-2016. Data were selected by purposive sampling method obtained 37 companies with 124 units analyses. Data collection techniques is documentary studies with collecting data that published by others. Moderated regression analysis by difference absolute value test was used to analyse data. Result of this research revealed that firm size and managerial ownership had significant effect on capital structure, while company growth and business risk did not have significant effect on capital structure. Profitability able to moderates significantly the effect of company growth and managerial ownership on capital structure, but unable to moderate the influence of business risk and firm size on capital structure. The research result, it can be concluded that capital structure is influenced by company growth, firm size, managerial ownership and profitability can moderate the effect of company growth and managerial ownership on capital structure.